AXIAL SPONDYLOARTHRITIS IN PATIENTS WITH CHRONIC BACKACHE USING ASSESSMENT OF SPONDYLOARTHRITIS INTERNATIONAL SOCIETY CRITERIA FOR AXIAL SPONDYLOARTHRITIS - Rasool, Tabe; Umer, Tahira Perveen; Nazir, Lubna; Arain, Shafique Rehman; Phulpoto, Kausar; Afzal, Warda (Journal of Ayub Medical College Abbottabad, 2018)
Background: Low back pain (LBP) is considered as one of the most frequent health problems which is responsible for forming a huge worldwide burden. This study was conducted with the aim to determine the frequency of axial-Spondyloarthropathy (axSpA) in patients presenting with chronic backache using Assessment of Spondyloarthritis International Society (ASAS) Criteria for axSpA. Methods: A total of 231 participants of either gender were enrolled with complaint of backache of more than or equal to 3 months duration and younger than 45 years. In the first stage, patients were interviewed and examined using standard questionnaire. In the second stage after going through laboratory investigations and imaging patients were classified into either axSpA (those meeting ASAS Criteria for axSpA) or non-SpA. Results: There were 65 males and 166 females. Mean age was 36.26 years. Eighty-nine (39%) patients were found to have axSpA as per ASAS Criteria. Majority of patients 70 (78.6%) in the imaging arm of ASAS Criteria were picked via MRI of sacroiliac joints. Peripheral arthritis was seen in 57 (64%) and Enthesitis in 52 (58.4%). Conclusion: MRI performed exceptionally to reveal sacroiliitis highlighting the importance of this imaging modality in axSpA, which we recommend to be included in diagnostic algorithm in evaluating patients with chronic backache under 45 years age. Keywords: Inflammatory backache; axial spondyloarthritis; Sacroiliitis;